When ADHD knocks on the door - discourse theory as a frame to explore subject positions and mental wellbeing before diagnosis - Grønneberg, Siv Vea; Engebretsen, Eivind; Torp Løkkeberg, Stine (International journal of qualitative studies on health and well-being, 2023)
Attention deficit hyperactivity disorder (ADHD) is currently the most prevalent childhood psychiatric diagnosis. This article reports how 10 young adults in Norway positioned themselves before they were diagnosed with ADHD either during early childhood or adolescence. A central theme is how these subject-positions relate to societal norms and mental well-being. Individual interviews were conducted, and the transcriptions of the interviews were analysed according to discourse theory. Six central subject positions were identified which in turn related to two major positions: 1) failure with schoolwork and 2) struggle in social interaction. The findings indicated specific emotional and environmental needs and that individuals were confronted with societal norms related to the criteria for ADHD prior to and regardless of whether one had received a formal diagnosis. We argue that analysing subject positions provides important knowledge regarding ADHD that is useful for individuals, parents, teachers, practitioners, policymakers, and helping professionals in the field of mental health and education when it comes to interventions that support children who possess different temperaments.